Age-related differences in kinematics and kinetics of sprinting in young female - Nagahara, R.; Haramura, M.; Takai, Y.; Oliver, J. L.; Wichitaksorn, N.; Sommerfield, L. M.; Cronin, J. B. (Scandinavian Journal of Medicine & Science in Sports, 2019)
This study aimed to investigate the age-related differences in sprinting performance, kinematic and kinetic variables in girls aged between 7.0 and 15.3 years. Step-to-step spatiotemporal variables and ground reaction impulses during sprinting were collected in 94 Japanese girls across a 50 m inground force plate system. From the results, a difference in rate of development in sprinting performance in girls over 12.7 years compared with younger girls (YG) was observed. The older girls (OG) became slightly slower each year (-0.09 m/s/y) compared to the YG (0.24 m/s/y) who increased their running speed. Moreover, height increased by 6.3 cm/y in YG and only 3.6 cm/y in OG, while step length during the maximal speed phase increased by 0.08 m/y in YG and plateaued in OG (0.01 m/y). Propulsive impulse during the initial acceleration phase was the kinetic variable to differ in rate of development between the age groups with an increase of 0.024 Ns/y in the YG compared to -0.010 Ns/y in OG. The development of sprinting ability in Japanese girls was more rapid before age 12.7 years. The difference in rate of development in sprinting ability can be primarily attributed to greater growth rates in YG, contributing to increases in the propulsive impulse during the initial acceleration phase and step length during the maximal speed phase. The limited gains in step length and the propulsive impulse in OG may reflect their reduced growth rate in height and the fact that increases in fat mass with maturation impaired relative force production.